Rehabilitation of Degraded Peat Swamp Forest in Raja Musa Forest Reserve, Selangor, Malaysia - Parlan, Ismail (2001)
Data from the Third National Forest Inventory shows there are about 0.23 million ha of logged-over peat swamp forests (PSF) in Peninsular Malaysia. It is important to improve the productivity of these areas by planting commercial tree species in order to sustain its role as an important source of high quality timber species. The main objectives of this study are to determine appropriate planting technique and identify suitable timber species to rehabilitate highly degraded PSF. Field planting that represents the core of the study was conducted in Compartment 101, Raja Musa Forest Reserve, Selangor, Malaysia. The area was classified as highly degraded PSF and occupied mostly by weeds especially Imperata cylindrica. Four different planting techniques were tested, namely open planting, open planting with mulching, open planting with topsoil and open planting with nurse tree. Six indigenous PSF species were used, namely Anisoptera marginata, Calophyllum ferrugineum, Durio carinatus, Ganua motleyana, Gonysty/us bancanus and Shorea p/atycarpa. Light intensity and foliar analysis were also measured. Light intensity was measured in the nursery to examine the response of the same species used in the field planting to different light intensities. Meanwhile, foliar analysis was conducted to compare the nutrient status of the seedlings among the four different planting techniques.